2016
DOI: 10.1007/s10494-015-9694-1
|View full text |Cite
|
Sign up to set email alerts
|

Heat Transfer Effects on a Fully Premixed Methane Impinging Flame

Abstract: A numerical assessment of different thermal conditions for an impinging flame configuration is investigated using large-eddy simulation. The cases of study correspond to a turbulent methane flame at equivalence ratio ER=0.8 and temperature T=298K exiting at 30 m/s with a nozzle-to-plate distance over diameter of H/D = 2. Computational cases based on different thermal conditions are compared to a conjugate case, in which fluid and solid domains are solved simultaneously. A solid material defined with enhanced c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…ATF with directly solved one-step chemistry was also implemented in LES [20] to evaluate the effects that different heat boundary conditions have on impinging flames. LES with detailed chemistry was carried out [21] and the result showed that significant difference occured in the deflection zone near the stagnation region.…”
Section: Introductionmentioning
confidence: 99%
“…ATF with directly solved one-step chemistry was also implemented in LES [20] to evaluate the effects that different heat boundary conditions have on impinging flames. LES with detailed chemistry was carried out [21] and the result showed that significant difference occured in the deflection zone near the stagnation region.…”
Section: Introductionmentioning
confidence: 99%
“…The present FSI model is implemented in Alya , BSC’s in-house multi-physics simulation software designed to run efficiently on supercomputers, exhaustively verified, validated, optimized and proved to give accurate solutions in complex fluid and solid mechanics problems, among other physics [51, 51, 52, 53, 54, 55, 45, 56]. Alya has been developed to scale efficiently in parallel on CPUs and/or GPUs using hybrid MPI, OpenMP, CUDA and/or…”
Section: Methodsmentioning
confidence: 99%
“…A low-dissipation finite-element method (FEM) implemented in the code Alya (Lehmkuhl et al, 2019). Alya (Vázquez et al, 2016) is a high performance computing multi-physics code extensively tested and proved to give accurate solutions in complex fluid mechanics problems (Mira et al, 2016;Calmet et al, 2016;Gövert et al, 2017;Rodriguez et al, 2019). For the convective term, a conservative Galerkin scheme proposed by Charnyi et al (2017), which preserves linear and angular momentum and kinetic energy at discrete level is used.…”
Section: Numerical Simulation Methodsmentioning
confidence: 99%